Economic factors of internal migration in the Republic of Kazakhstan: problems and challenges - Bokayev, B.; Akhmetova, G. (BUKETOV BUSINESS REVIEW, 2024)
Abstract: Objective: This study aims to analyze and evaluate the effectiveness of economic instruments to manage internal migration in the country. The study aims to examine the economic factors influencing migration patterns in order to identify the potential role of economic incentives and policies in addressing issues related to internal migration. Methods: Statistical and thematic analysis are used to identify the motives that drive people to move from one region to another within the country. Results: Preliminary results indicate that economic factors, such as differences in income, employment opportunities and standard of living, have a significant impact on the decision to migrate within a country. The article analyzes the impact of tax benefits and improvement of housing conditions for migrants Analysis of the ratio of demand and supply in the labour market regions, gross regional product per capita and other indicators. The results of the empirical research thus contribute to the available scientific literature on migration management and the influence of economic factors on migration processes. Conclusions: When designing public policies in the field of migration and regional development, the findings of this study, when implemented, can improve the effectiveness of these policies. The results of the study showed that not all measures and conditions have an equal effect on migration. And there are other factors besides economic factors that are equally important.